2015
DOI: 10.1037/hea0000187
|View full text |Cite
|
Sign up to set email alerts
|

Racial and sexual identities as potential buffers to risky sexual behavior for Black gay and bisexual emerging adult men.

Abstract: Researchers and interventionist should consider the ways in which racial centrality may be a critical tool in our efforts to decrease the HIV epidemic among young Black gay and bisexual men in America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Prior research has also demonstrated that positive views of gay identity can be protective among gay youth and are often associated with favorable health outcomes despite concomitant stresses. 34,35 In addition to these assets, social support satisfaction emerged as a significant predictor in our model and is a well-described resilience resource in adolescence and young adulthood. 16 This has also been shown in studies focused on sexual and ethnic minority youth and their communities.…”
Section: Discussionmentioning
confidence: 97%
“…Prior research has also demonstrated that positive views of gay identity can be protective among gay youth and are often associated with favorable health outcomes despite concomitant stresses. 34,35 In addition to these assets, social support satisfaction emerged as a significant predictor in our model and is a well-described resilience resource in adolescence and young adulthood. 16 This has also been shown in studies focused on sexual and ethnic minority youth and their communities.…”
Section: Discussionmentioning
confidence: 97%
“…These factors can sometimes buffer the negative effect of existing within multiple marginalized identities. For example, prior work suggests that for some YBGBM a positive societal view of Black men was associated with decreased sexual risk behavior [89]. …”
Section: Cultural Norms/expectationsmentioning
confidence: 99%
“…Prior work suggests for some young Black gay and bisexual men high racial centrality and racial public regard (beliefs about how society views Black people) was associated with decreased sexual risk behavior including condomless anal intercourse [89]. …”
Section: Figurementioning
confidence: 99%
“…In addition to what has been previously mentioned, from a societal perspective, we must acknowledge how the pervasive distal scourge of racism relates to HIV prevention, with medical and public health systems working on eradicating discrimination within medical spaces and acknowledging the impact of racism on health inequities among YBMSM [117]. Highlighting the intersection of racial and sexual identities is paramount as we know that embracing both is key to wellness among YBMSM [118]. Initiatives should also emphasize the roles that gender norms and religious doctrines/beliefs play in the overall health and lived experiences of YBMSM [92,119] [27,120] [121,122].…”
Section: Focus On Distal Determinants Of Healthmentioning
confidence: 95%